Kecemasan terhadap Pernikahan pada Perempuan Dewasa Awal yang Mengalami Fatherless - Junaidin Junaidin; Kartika Mustafa; Syafiya Khoirunnisa; Roni Hartono (Departement of Mathematics Education, 2023)
Women in a fatherless state have a condition of fear of being abandoned, the same as what their father had done, causing anxiety to make a commitment or marriage. Anxiety is an emotional experience that arises because of a threat that has no clear cause, both from outside and from within the individual. This study aims to find out and describe how anxiety about marriage in early adult women who experience orphans with descriptive research methods. In collecting data, researchers used semi-structured interview techniques and unstructured observation. The research subjects were three early adult women aged 19-25 years. The results of this study indicate that women who experience fatherlessness have anxiety about marriage. The third subject has a negative perception of the opposite sex, thus affecting her image of marriage. The third subject also uses their verse as a benchmark for men they should stay away from. Even though the father should be the first man for the daughter who is a good example in the future. This is one of the factors that makes the third subject have anxiety about marriage.